Potential Pareto Optimality of Risky Projects - O'Flaherty, Brendan (Quarterly Journal of Economics, 1986)
Journal Article Potential Pareto Optimality of Risky Projects Get access Brendan O'Flaherty Brendan O'Flaherty Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 101, Issue 3, August 1986, Pages 647–651, https://doi.org/10.2307/1885704 Published: 01 August 1986